Effects of aerial exposure on antioxidant defenses in the brown mussel Perna perna - Almeida,Eduardo Alves de (2006)
Investigations were carried out to evaluate the antioxidant defenses in digestive gland of mussels Perna perna held in air for 4 hours, exposed to air for 4 hours followed by submersion in water for 30 minutes, and constantly submerged for 4.5 hours. No differences were observed in CAT and GPx activities and in the levels of total GSH. Mussels exposed to air had significantly higher SOD activity, possibly related to a preparative mechanism of defense against oxidative stress during reoxygenation.